Public Interest Environmental Litigation: Recent Cases Raise Possible Obstacles - M Kidd (Potchefstroom Electronic Law Journal, 2010)
Despite the broadening of locus standi in environmental cases by both Section 38 of the Constitution of the Republic of South Africa, 1996, and Section 32 of the National Environmental Management Act 107 of 1998, two recent cases suggest that the preconstitutional approach to locus standi still holds sway in our Courts. Moreover, failure to recognise the environmental right in Section 24 of the Constitution may be an impediment to applicants' ability to bring an interdict application successfully. Correct use of the relevant constitutional provisions ought to obviate such problems, but alternatives are suggested. In the course of the article, it is suggested that the rule in Patz v Greene is no longer relevant and should be consigned to the history books.